PROKRASTINASI AKADEMIK PADA MAHASISWA - Musslifah, Anniez Rachmawati (TALENTA, 2014)
ABSTRACTProcrastination  or  procrastinate  in  doing  and  completing  academic  tasks  is  a common practice by most students, including working and completing thesis. Thesis is a task that must be completed by each student as a condition of graduation. Many fact ors cause students perform procrastination, ranging from delaying the start or finish a task, overdue tasks, and the gap between planned and actual performance.This  study  aims  to  look  at  the  level  of  academic  procrastination  in  students  of psychology faculty Muhammadiyah University of Surakarta. The subject of research is a graduate  student  in  the  school  term  of  more than  10  semesters  or  five  years  and  have taken courses thesis over 2 semesters or 1 year.Results  of  this  study  that  the  level  of  procrastination  in  students  of  psychology faculty of the University of Muhammadiyah Surakarta moderate.Keywords: Academic Procrastination, thesis, students